REHABILITASI TERUMBU KARANG AKIBAT PENGEBOMAN DENGAN METODE TRANSPLANTASI MENGGUNAKAN KARANG JENIS Acropora sp. - H, Harianto; M, Musrin; A., Asri (Program Kreativitas Mahasiswa - Pengabdian Kepada Masyarakat, 2013)
Coral reefs are ecosystems which have the diversity of fauna and productivity high. Besides coral reef ecosystems is also a place to live, a place foraging (feeding ground), care area (nursery ground) and spawn (spawning ground) for a variety of marine life. In the village Sinaulu Jaya is one of the areas that have the potential for major coral species Acropora sp, but due to the activities of the local people in fishing activities in ways that are not environmentally friendly such as the use of bombs that make coral reefs in this area many degraded or damaged. To address the sustainability of catching up with the environmentally unfriendly then the initiative to socialize and transplantation.